2015
DOI: 10.1007/s00432-015-1985-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of cancer stem-like cell markers in high-grade neuroendocrine carcinoma of the lung

Abstract: The differences in the expression profiles of CSLC markers might reflect morphological differences between SCLC and LCNEC. Positive ALDH1 expression in lung HGNEC was associated with an unfavorable patient prognosis, which suggested that ALDH1-positive tumor cells might be future therapeutic targets for the treatment of lung HGNEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The role of FOXD3 in stem cells is further demonstrated by facilitating the exit from naive pluripotency and transition to a primed pluripotent state . Recent studies have suggested parallels between embryonic stem cells and TICs, which is highlighted by the shared transcription factors involved . The deregulation of FOXD3 is implicated in the tumorigenesis of gastric cancer, melanoma, and breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…The role of FOXD3 in stem cells is further demonstrated by facilitating the exit from naive pluripotency and transition to a primed pluripotent state . Recent studies have suggested parallels between embryonic stem cells and TICs, which is highlighted by the shared transcription factors involved . The deregulation of FOXD3 is implicated in the tumorigenesis of gastric cancer, melanoma, and breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the CSC marker Nanog upregulates FAK, which, in turn, phosphorylates Nanog in CRC cell lines [59]. Upregulation and activation of FAK has also been observed in the presence of Oct 3/4-surexpressing glioblastoma primary cell cultures [245]. CD133, another CSC marker, enhanced cells migration through Src-FAK signaling activation [246].…”
Section: Regulation Of Cancer Stem Cellsmentioning
confidence: 99%
“…It was interesting to detect differences in CD44, ALDH1 protein and STAT3 gene expression between the UWG02CTC and UWG02ASC, which probably reflects the different pathways of tumour cell dissemination. Of note, higher expression of CSC markers and key stem pathways was also found on UWG02CTC versus UWG01CTC, despite ALDH1, CD44, and CD133 reported as CSC markers in both adenocarcinomas and high grade neuroendocrine tumours 33,34 .…”
Section: Discussionmentioning
confidence: 88%